If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11y + 2y = 0 Combine like terms: 11y + 2y = 13y 13y = 0 Solving 13y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '13'. y = 0 Simplifying y = 0
| -(-40)+m=65 | | 3(y-2)=6y+1-2(-6y-1) | | 9*57= | | 6x=3x+-2+28 | | 95=5(2-y) | | 3000/40-40x= | | 3a+5b=14 | | -5x+2=x+26 | | 2m+(3+4)=19 | | 224/32 | | 12*44= | | 90=b+45 | | -[7z-(15z+9)]=9+(7z+5) | | 9x=-(27/7) | | x+84=114+x | | f(x)=2240x-16x^2 | | 3(x-3)+2(3x+1)=11 | | 125*9*16= | | -4x-4=2-7x | | 4/5x=-1(3/5) | | 15+a=21 | | 6x+7-2x+4=49(-3x-5)-17 | | (x^2/3)-5=7 | | M+79=78 | | 4=(P1-5)/40 | | 4(9-x)=60 | | 127=-7x-6x+10 | | 9x+17-3x=12+4x+5 | | -(3x+8)=-10 | | 6x+7-2x+4=4(9-3x-5)-17 | | -3r+9=-4r+6 | | Y/4=x-50 |